Evaluation of ameliorative effect of sodium nitrate in experimental model of streptozotocin-induced diabetic neuropathy in male rats - Oghbaei Hajar (Sciendo, 2019)
Objective. Diabetes induces sensory symptoms of neuropathy as positive (hyperalgesia), negative (hypoalgesia), or both.